Exploring Digital Misinformation as a Sociotechnical Phenomenon: Insights from a Small-scale Study - Puska, Alisson Andery; Pereira, Roberto (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
This article addresses the challenge of comprehending digital misinformation as a sociotechnical phenomenon within the field of Human-Computer Interaction, particularly in the context of COVID-19-related misinformation in Brazil. The study employed an exploratory approach to analyze misinformation cases using various artifacts and conducted a focus group with eight experts in the field. The findings revealed 137 sociotechnical aspects and 29 stakeholders, shedding light on the complex interplay of factors influencing digital misinformation's creation, dissemination, and consumption. The study emphasizes the necessity of adopting a sociotechnical approach and highlights the challenges in comprehensively analyzing stakeholders, communication channels, and the stages of the misinformation lifecycle. Overall, the research contributes to a deeper understanding of digital misinformation in sociotechnical contexts and its implications for Human-Computer Interaction.